Dairy Farming in Wisconsin During the Depression: The Milk Strikes of 1933 - Keene, Andrew (My University, 2018)
This paper will discuss the Wisconsin Milk Strikes of 1933. To understand what happened during the Milk Strikes, this paper will go over a general history of farming in the state up to the Depression in 1933. Upon understanding the history, it will dive deeper into what was going on in 1933, and explain what caused the Milk Strikes and how they came to an end.
Keywords: Wisconsin--Economic conditions; Dairying--Economic aspects--Wisconsin--History; Strikes and lockouts--Dairying--Wisconsin; Agriculture and state--United States--History--20th century; Depressions--1929--Wisconsin